2018
DOI: 10.1108/jmh-06-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing the reinvention of operations management

Abstract: Purpose The purpose is to provide an intellectual history of Operations Management, particularly noting recent developments and its underlying continuity with earlier systems and thinking. Operations Management as a discipline identifies its “modern” incarnation as dating from the 1960s when it became more rigorous and managerially focused. This re-invention constructed a “narrative” that the profession still follows, yet a critical perspective reveals significant, though under-appreciated continuity with earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 107 publications
(176 reference statements)
0
7
0
1
Order By: Relevance
“…There was no ignorance about demand levels and the value of managing production and inventory in relation. Figure 4, for example, illustrates how production was closely matched to highly variable sales, while minimizing inventories (Wilson, 2018). In the Ford factories there were multiple production lines, some of which could be temporarily closed or reopened depending upon demand volumes.…”
Section: Supply Chain Lessons That Henry Ford Does Not Normally Get Credit Formentioning
confidence: 99%
“…There was no ignorance about demand levels and the value of managing production and inventory in relation. Figure 4, for example, illustrates how production was closely matched to highly variable sales, while minimizing inventories (Wilson, 2018). In the Ford factories there were multiple production lines, some of which could be temporarily closed or reopened depending upon demand volumes.…”
Section: Supply Chain Lessons That Henry Ford Does Not Normally Get Credit Formentioning
confidence: 99%
“…This was a short-lived period of modernization because the shift turned out to be ineffective. Wilson (2018) observed that with the shift, practical ideas shared by practitioners which dominated in the past became neglected or ignored. These were replaced by "theoretical constructs of an abstract reality" expressed in OR models which were then analyzed to produce optimized results "written in arcane jargon published in low circulation."…”
Section: Modern Operations Managementmentioning
confidence: 99%
“…In contrast to traditionally standardized production, where producer impose their standard products to customer, customized production is flexible, the products are adapted to the very customer's demand. Customer product can be perceived as a product modified according to customer's needs (Wilson, 2018;Fiorentino, 2018). Customization generates higher product differentiation, which furtherly leads to product diversity increase, and starts with negotiations with the customer on the details of the order, which continue in the course of design, production and sale of the product.…”
Section: Formingmentioning
confidence: 99%